Arsitektur Islam : pemikiran, diskusi, dan pencarian bentuk - Utaberta, Nangkula (Bulaksumur, Yogyakarta : Gadjah Mada University Press, 2008)
On Islamic architecture of mosques and public buildings in Indonesia and Malaysia.
Includes bibliographical references (p. [135]-151).
Originally presented as the author's thesis (master's--Universiti Teknologi Malaysia, 2004) under title: Ke arah arsitektur Islam yang berbasiskan sunnah, sebuah pengambilan pelajaran dari ide arsitektur organik Frank Lloyd Wright.
Koleksi Sumbangan : Abdul Ghafar Ibrahim (AGI)
Keywords: Islamic architecture -- Malaysia; Islamic architecture -- Indonesia